INDIGENOUS HERBAL PLANTS USED BY TRIBES OF RAJASTHAN FOR IMPROVING SEXUAL PERFORMANCE AND PROBLEM ASSOCIATED WITH SEXUALITY (International Journal of Food and Nutritional Sciences, 2023)
The aim of present study was to summaries the literature on medicinal plants preparedby survey on indigenous knowledge of tribes of Rajasthan on traditional medicinal plantsused by them for improving their sexual performance and problem associated with sexuality.